(untitled) (Cultura Económica, 2019)
Reseña del libro A History of Balance 1250-1375. The Emergence of a New Model of Equilibrium and its Impact on Thought de Joel Kaye. Cambridge University Press – Cambridge, 2014. ISBN: 1107028450